Le Mouvement moderne aux champs. De la Ferme radieuse au Regional Planning - Guillemette Morel Journel (In Situ, 2013)
For the 20th century architect, rural territories seem to be a “no-go” area. In particular, so-called “modern” architects seldom show an interest in the construction of farms and the planning of the countryside. Le Corbusier (1887-1965) is an exception in this regard and from 1930 onwards he perfected the concept and the formalisation of the “radiant farm”. The consequence of the latter in the 1940s was the doctrine of the Three Human Establishments, which also derived from the systematics of the Athens Charter. Both Outre-Atlantique, a much less well-known figure in the Modern Movement and Ludwig Hilberseimer from Germany (1885-1967), who emigrated to Chicago after having taught at the Dessau Bauhaus, reflected on this question, publishing The New Regional Pattern in 1949. The sub-title of this richly illustrated work – Industries and Gardens. Workshops and Farms – indicates that the rural scale formed an integral part of the proposal of he who had devised the spectacular and totally mineral project of HochStadt in 1924. How was it that such pillars of the “Modern Movement”, focussed only on the City, came to lean towards rural areas? Did they reconcile their approach to a territory about which they knew very little with their yearning for novelty and their taking into account a population which they presumed to be reactionary? Did their opinions exert any influence on rural planning, and did they have any disciples?